HGG-32. Durable response to mTOR inhibitor after failing Checkpoint inhibitors in Ultra-Hypermutated High grade glioma in context of CMMRD. (3rd June 2022) - Hegde, Kriti; Dahl, Christine; Depani, Sarita; Hargrave, Darren; Oostveen, Minou; Aguirregomezcorta, Fernando; Jeelani, Owase; Aquilina, Kristian; Gains, Jenny; Ching, Yen; Jacues, Thomas; Merve, Ashirwad; et al.
Abstract: BACKGROUND: Paediatric High Grade Gliomas (HGG) have poor outcomes with conventional treatment. HGG in association with constitutional DNA mismatch repair deficiency (CMMRD) are hypermutated and have shown dramatic response to checkpoint inhibitors. Salvage following progression or failure to respond to check point inhibitors has rarely been reported. We describe a successful alternative therapeutic approach targeting the activated pathway (mTOR) in a hypermutated HGG. CASE SUMMARY: A 6-year-old girl presenting with seizures was diagnosed with left frontal lobe HGG with concurrent neck mass (Pilomatrixoma). Presence of synchronous tumours raised the possibility of cancer predisposition; the HGG was hypermutated with germline PMS2 mutation confirming diagnosis of CMMRD. Near total resection was undertaken followed by focal radiotherapy 54 Gy, with 1 cycle of concomitant CCNU. MRI post radiotherapy showed tumour progression. Anti-PDl inhibitor Nivolumab was commenced. CTLA-4 antibody, Ipilimumab was added after 4 cycles of Nivolumab due to poor response. Tumour response was seen, but dual therapy had to be discontinued due to toxicity. The tumour progressed following further single agent Nivolumab. In view of multiple mutations in the mTOR pathway (NF1, PIK3/PTEN, TSC1, TSC2), a mTOR inhibitor, Everolimus was commenced. There was 25% tumour reduction after 4 weeks treatment and further reduction after 6 months. Resection of residual tumour showed necrotic tissue only. There continues to be a sustained response to Everolimus for over 12 months. DISCUSSION: Approximately a third of CMMRD HGG respond to checkpoint inhibitors. For those that don't, these hypermutated tumours offers the possibility of targeting specific molecular pathways. Response to Everolimus in HGG harbouring mTOR aberrations have been described. To our knowledge this is the first report of successful use of mTOR inhibitor in CMMRD HGG. CONCLUSION: Targeted molecular treatment for patients with CMMRD hypermutated brain tumours should be considered according to the mutated pathways.